Integration of Sustainability Principles in Natural Resource Management in Agroforestry Areas - Judijanto, Loso; Suwarna, A. Idun (Westscience Press, 2025)
Agroforestry systems represent a critical approach to integrating sustainability principles in natural resource management. This study analyzes 10 Scopus-indexed documents to explore the practices, challenges, and opportunities in agroforestry. The findings reveal the significant role of agroforestry in promoting biodiversity, improving soil fertility, and mitigating climate change through sustainable practices such as circularity, agroecological transitions, and community engagement. However, challenges such as limited access to technology, policy gaps, and socio-economic barriers remain persistent. Integrating traditional ecological knowledge with modern technologies and fostering inclusive governance models are identified as pivotal strategies for enhancing agroforestry’s sustainability. The study highlights the importance of addressing trade-offs between ecological, economic, and social dimensions to unlock agroforestry's full potential in achieving global sustainability goals.